Implementasi Fatwa MPU Aceh No. 9 Tahun 2013 Pada Perusahaan Tambang di Provinsi Aceh - Ariful Mufti (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2023)
Aceh as one of the provinces in Indonesia which is famous for its area that stipulates Islamic law as a whole in all aspects, be it the relationship between humans and with Allah SWT. This is evidenced by the existence of special sharia rules or called Qanun set by the MPU. These rules must of course be accompanied by appropriate practices, not limited to a single product. The practice in question is, carrying out all kinds of rules that have been established as a society with the application of applicable law. The implementation of zakat has encountered many obstacles because it is still not followed by an adequate level of understanding on how to implement zakat. The lack of understanding of the types of assets that are obligatory on zakat and the payment mechanism guided by Islamic law causes the implementation of zakat worship to be highly dependent on each individual. The type of research that the writer uses is descriptive qualitative research with the method of case studies (case studies) and field studies (field research). In this study, the authors conducted a study directly in the field to obtain concrete data regarding the preparation for mining zakat in Aceh. The research approach that will be used in this paper is a normative juridical approach and an empirical juridical approach. The rules regarding zakat in Aceh itself are certainly sufficient, especially on mining zakat, as written in Aceh Qanun Number 10 of 2012, but the practice of enforcing Qanuns faced by the current government is still the main factor in hampering the process of collecting and distributing zakat. there are still many groups who think that zakat on mining goods is the same as trade zakat, which is then paid by the company when it reaches the haul. As for the mining zakat itself, scholars have ordered that your haul is not set.